UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR VOKAL DAN DRUM PADA KEGIATAN EKSTRAKURIKULER BAND DENGAN METODE EAR TRAINING PADA SISWA SMP N 3 SEMARANG - Setiawan, Nanang; raharjo, eko (Universitas Negeri Semarang, 2015)
Students prefer an easier way to learn the vocals and drums on the band's extracurricular activities, from a sense of love that the interests of students can grow so that the results belajarpun also increased. The purpose of this study was to determine whether using the method of ear training can increase interest and learning outcomes vocals and drum band students in extracurricular activities SMP N 3 Semarang. This type of research is a classroom action research with two cycles were carried out on students of SMP N 3 Semarang. The first cycle and the second cycle consists of planning, action, observation, and reflection. Data collection techniques used include practice tests, questionnaires, observations, journals, documentation, and interviews. Data analysis technique used is the percentage descriptive analysis, analysis of reflection, and discussion of evaluative. These results indicate that by using the method of ear training can increase interest and learning outcomes vocals and drum students of SMP N 3 Semarang on the band's extracurricular activities. Improvement occurs in both the interest and the learning outcomes for the use of ear training methods can facilitate students in learning vocals and drums on the band's extracurricular activities, so as to ease the students feel happy and interested in learning vocals and drums.